Phytotoxicity of low doses of dicamba when sprayed in pre-emergence on non-tolerant soybean - Carvalho, Saul Jorge Pinto de; Magalhães, Túlio Braga; Ovejero, Ramiro Fernando López; Palhano, Matheus Gabriel (Revista de Ciências Agroveterinárias, 2022)
Soybean transgenic cultivars provide a new alternative for elaborating weed management programs once they allow the application of herbicides previously considered non-selective to the crops, and between them, dicamba. However, it is well known that non-tolerant cultivars are extremely sensitive to this herbicide due to spray drift or incorrect tank wash, which may promote severe injuries to the crop. Therefore, this work was developed to evaluate the susceptibility of dicamba non-tolerant soybean submitted to simulated drift of this herbicide in pre-emergence conditions. Three experiments were conducted, two inside a greenhouse and one in field condition. A randomized block design was adopted with four replications each. In the greenhouse, soybean cultivars Agroeste AS 3590 IPRO and Nidera 7709 IPRO were evaluated, simulating seven and six doses of dicamba, respectively. On the field, cultivar Monsoy 5917 IPRO was adopted, with six doses of dicamba. In general, besides soybean cultivar, visual symptoms were observed on plants up to 3.75 g ha-1 of dicamba, and 60 g ha-1 might be considered as the critical doses. Bellow this dose, plants were able to recover from symptoms; however, above this dose, a reduction on mass of dry matter was observed. In field conditions, no yield losses were observed for soybean, regarding the doses evaluated.